KESADARAN LINGKUNGAN DI KALANGAN SANTRI TERHADAP PEMBANGUNAN BERKELANJUTAN - Fachruddin M. Mangunjaya; Hadi S. Alikodra; Akhmad Arif Amin; Ahmad Sudirman Abbas (Media Konservasi, 2013)
This study aims to identify the level of awareness of the concept of sustainable development among middle high school students at three Islamic boarding schools (pesantren). The survey was conducted with 514 respondents (level XI) from Pesantren Daar El Qolam (Tangerang), Pesantren Al Musaddadiyah (Garut) dan Pesantren Buntet (Cirebon). Dependent variables were the level of environmental awareness of the concept of sustainable development and practices: i.e. Sustainability practices awareness and behavioral and attitudinal awareness, environmental education and Islamic environmentalism. Independent variables were the three types of pesantrens above. The research instrument used was the questionnaire, using a Likert scale. The method of analyzing data was descriptive, Spearman Correlation and one-way Anova, using SPSS software ver. 11.0. Research outcomes showed that all the students from the three pesantren institutions indicated that they have a moderate level of sustainable development awareness (mean=3.86; sd=0.86). They also believe Islam teaches about environment -- Islamic environmentalism –giving guidance on good practice toward the environment (90.38%). Unfortunately their environmental theory gained from schools was not related to their daily attitude, which in turn related to their behavioral awareness (ρ=0.024). They rarely practice in the level of sustainability practice awareness (52%), and behavioral attitude and awareness (62%). But emotionally they have a high concern to the environmental problems (89%). The One-Way Anova showed there were differences between the three institutions in teaching about the environment, Islamic environmentalism and behavioral attitude awareness, but there were no differences between sustainability practice awareness and emotional awareness. Keyword: environmental awareness, sustainable development, Islamic environmentalism, sustainability practice, behavioral and attitude awareness